2008
DOI: 10.1007/s11249-008-9401-7
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Quantitative Determination of Ultra-low Wear Rates of Materials, Part I: On Steels

Abstract: A novel method for the quantitative determination of the wear of materials at very low wear rates is introduced here. The main concept involves implanting gold as a trace marker into the tested materials, and measuring the gold concentration and depth profile before and after the wear tests by Rutherford backscattering (RBS). The amount of gold loss is related to the material loss under the tested conditions. The background concentration of gold in AISI 1095 and 52100 steels has been determined by neutron acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The low-wear-rate method has been introduced and discussed extensively in Part I [10]. The main steps of the method are: (1) implantation of Au as a marker into the tested materials; (2) measurement of the amount and profile of Au by carbon-Rutherford backscattering spectroscopy (C-RBS); (3) wear testing of the implanted samples and (4) re-measurement of the amount and profile of Au by C-RBS and then calculation of extent of the loss of the gold during the wear process.…”
Section: Low-wear-rate Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The low-wear-rate method has been introduced and discussed extensively in Part I [10]. The main steps of the method are: (1) implantation of Au as a marker into the tested materials; (2) measurement of the amount and profile of Au by carbon-Rutherford backscattering spectroscopy (C-RBS); (3) wear testing of the implanted samples and (4) re-measurement of the amount and profile of Au by C-RBS and then calculation of extent of the loss of the gold during the wear process.…”
Section: Low-wear-rate Methodsmentioning
confidence: 99%
“…Many studies have shown that surface texturing offers good performance from the boundary lubrication to hydrodynamic lubrication regimes [7][8][9]. Our new low-wear-rate method (see previous paper; [10]) was applied to further understand the behaviour of surface texture on wear performance.…”
Section: Introductionmentioning
confidence: 99%